Efficacy of cefotaxime combined with gamma globulins on C-reactive protein and procalcitonin in neonatal sepsis - Zhang, Fan (Cellular and Molecular Biology, 2020)
C-reactive protein (CRP) is encoded by CRP or PTX1 gene and procalcitonin (PCT) is produced by the CALC-1 gene induction. Both PCT and CRP are known as valued biomarkers markers in prediction of Serious Bacterial Infections (SBI) in children. This experiment carried out to analyze the efficacy of cefotaxime combined with gamma globulins on neonatal sepsis and the effect on CRP and PCT. For this purpose, a total of 120 sepsis children were selected and randomly divided into observation and control groups. Children in the control group were treated with cefotaxime, while children in the observation group were treated with cefotaxime combined with gamma globulins. The two groups were compared in terms of the relative measures of efficacy, the total effective rate of treatment, the incidence of complications and serum CRP and PCT levels before and after treatment. The clinical measures of the observation group were all lower than those of the control group, and the total effective rate of the treatment was higher than that of the control group, while the incidence of complications was lower than that of the control group. In addition, before treatment, there was no difference in CRP and PCT between the two groups; after treatment, the above measures in the observation group were lower than those in the control group. It is concluded that Cefotaxime combined with gamma globulins in the treatment of neonatal sepsis has significant efficacy and is clinically more effective than cefotaxime monotherapy. This combination can shorten clinical symptom remission time and hospital stay, improve serum CRP and PCT levels and promote the recovery of children, worthy of promotion.